Evaluation of direct rapid prototyping pattern for investment casting - Omar, Mohd. Faizan Marwah (2012)
The ability of rapid prototyping (RP) technology t o fabricate direct part of any complex shape as a sacrificial pattern in shorter lead time has benefited the foundry industries significantly . The quality of investment casting (IC) parts is dir ectly related to the master pattern fabricated from RP process. The main objective of this study was to evaluate the quality characteristics of various RP patterns that were fabricated by various RP process es which include 3D Printer (3DP), Fused Deposition Modeling (FDM) and Multijet Modeling (MJ M). Evaluation of the RP patterns was carried out on dimensional accuracy, surface roughn ess and pattern shrinkage. Different internal pattern designs for the RP parts were developed usi ng Insight software for FDM process and Solidworks 2011 for other RP systems. In addition t o the quality assessments, the effect of the internal pattern designs on the burn out behaviour of the RP patterns was also evaluated. Experimental results showed that FDM and MJM produc ed patterns with better accuracy, surface roughness and part shrinkage when compared to 3DP. It was evident that the internal pattern structure improved the accuracy of the patterns produced from all RP processes. Results showed that FDM and MJM processes were superior in terms of mold cleanl iness when no residual ash was observed during the burn out stage. Significant oxidation of cerami c powder was observed on the molds of the 3DP patterns which need to be removed manually from the molds